Protective Effect of Morphine Against the Oxidant-Induced Injury in H9c2 Cells - Skrabalova, Jitka; Karlovska, Ivana; Hejnova, Lucie; Novotny, Jiri (Cardiovascular toxicology, 2018)
There are some indications that morphine may exert myocardial protective effects under certain conditions. The aim of the present study was to investigate the effect of morphine on viability and oxidative state of H9c2 cells (rat cardiomyoblasts) influenced by oxidative stress that was elicited by exposure to tert-butyl hydroperoxide (t-BHP). Our experiments showed that pretreatment with morphine before the addition of t-BHP markedly improved cell viability. Morphine was able to increase total antioxidant capacity of H9c2 cells and to reduce the production of reactive oxygen species, protein carbonylation, and lipid peroxidation. Cellular damage caused by t-BHP was associated with low levels of p38 MAPK and GSK-3β phosphorylation. Pretreatment with morphine augmented p38 phosphorylation, and the increased phospho-p38/p38 ratio was preserved even in the presence of t-BHP. Morphine did not change the level of GSK-3β phosphorylation, but interestingly, the phospho-GSK-3β/GSK-3β ratio significantly increased after subsequent incubation with t-BHP. Furthermore, morphine exposure resulted in upregulation of the antioxidant enzyme catalase. The protective effect of morphine was abrogated by the addition of the PI3K inhibitor wortmannin and/or p38 MAPK inhibitor SB203580. It can be concluded that morphine may protect H9c2 cells against oxidative stress and that this protection is at least partially mediated through activation of the p38 MAPK and PI3K/GSK-3β pathways.
Keywords: Phosphatidylinositol 3-Kinase; oxidační stres; antioxidancia; karbonylace proteinů; Cell Line; Reactive oxygen species; Oxidative stress; mitogenem aktivované proteinkinasy p38; Morphine; fosforylace; GSK-3β; Oxidants; signální transdukce; Phosphorylation; terc-butylhydroperoxid; Glycogen Synthase Kinase 3 beta; cytoprotekce; Protein Carbonylation; nekróza; Cytoprotection; Signal Transduction; krysa rodu Rattus; Tert-butyl hydroperoxide; kardiomyocyty; Animals; Necrosis; morfin; Antioxidants; p38 Mitogen-Activated Protein Kinases; zvířata; Rats; Myocytes, Cardiac; p38 MAPK; peroxidace lipidů; buněčné linie; apoptóza; Lipid Peroxidation; H9c2 cells; Oxidative Stress; 1-fosfatidylinositol-3-kinasa; oxidancia; kinasa glykogensynthasy 3beta; Apoptosis; tert-Butylhydroperoxide